Kinerja karyawan hotel bintang 4 dan bintang 5 di Bandung Raya - Dewi Kania; Mudayat Mudayat (Amal Insani Foundation, 2022)
This study aims to analyze and study descriptively and derivatively related to the Influence of organizational culture and organizational commitment on job satisfaction and employee engagement and its implications on employee performance. This research method is a quantitative research method with descriptive and explanatory survey methods with crossectional categories. Population based on the geographical area with sampling techniques using proportional stratified random sampling. Sources of data obtained from Primary and Secondary data through observation, questionnaires, interviews and documentation using data analysis techniques, namely Path Analysis. The results showed that descriptively organizational culture is in the exceptionally good to a suitable category, while organizational commitment is in the relatively good to the excellent category, then job satisfaction is in the good enough to the good category, and employee engagement and employee performance are also in the category of good enough to sound, and the whole hypothesis is accepted.